Implementation of IEEE 802.11p for Vehicular Communication: Utilizing NI USRP N321 to Advance Mobile Interactive Technologies - Telagam, Nagarjuna; Y.L. Ajay Kumar; V.R. Seshagiri Rao; Nanjundan, Menakadevi; Seetha Chaithanya; Kandasamy, Nehru (International Journal of Interactive Mobile Technologies (iJIM), 2025)
This paper aims to comprehensively implement the Institute of Electrical and Electronics Engineers (IEEE) 802.11p transceiver using the Universal Software Radio Peripheral (USRP) device N321 series for teaching undergraduates. It is a standard in the 802.11 family designed explicitly for wireless access in vehicular environments (WAVE). This process involves configuring the USRP N321 device with IEEE standards, such as adjusting the frequency, amplitude, transmitter gain, direction of the radiation pattern, receiver gain, etc. This transceiver uses an orthogonal frequency division multiplexing (OFDM) modulation scheme. This IEEE 802.11p transceiver provides a practical approach for students and researchers in the realworld platform to analyze wireless communication technologies such as OFDM transceiver, peak-to-average power ratio (PAPR) values, and constellation diagrams for various modulation schemes such as binary phase shift keying (BPSK), quadrature amplitude modulation (QAM), and quadrature phase shift keying (QPSK) with different code rates. The bit error rate values were calculated for the modulation coding schemes index, and data rates of 24 Mbps were achieved for this transceiver.